The Relationship Between Spirituality and Anxiety Levels in Third-Trimester Pregnant Women - Syafiq Putra Adiyatma; Nasrudin Andi Mappaware; Susdiaman; Muhammad Alim Jaya; Zulfitriani Murfat (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
The third trimester is a phase of pregnancy that is prone to increased anxiety before delivery, and spirituality is thought to play an essential role in helping to reduce this anxiety. This study aims to analyze the relationship between spirituality levels and anxiety levels in pregnant women in the third trimester. This study employed an analytical observational design with a cross-sectional approach and was conducted at RSIA Sitti Khadijah 1, Muhammadiyah Branch, Makassar, from November 10 to December 8, 2025. This study employed a total sampling approach to recruit 31 pregnant women in the third trimester who met the inclusion criteria. Spirituality levels were measured using the Daily Spiritual Experience Scale (DSES), and anxiety levels were measured using the Generalized Anxiety Disorder-7 (GAD-7). The results showed that most respondents had minimal anxiety levels (77.4%) and high spirituality levels (83.9%). The correlation test results showed a significant relationship between spirituality levels and anxiety levels (p = 0.000). This study suggests that higher spirituality is associated with lower anxiety levels. Therefore, it can be concluded that spirituality plays a vital role in helping pregnant women manage anxiety before childbirth and can be considered as part of a holistic approach to antenatal care.